1998
DOI: 10.1001/archinte.158.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Methicillin Resistance on the Outcome of Patients With Bacteremia Caused by Staphylococcus aureus

Abstract: Methicillin resistance in patients with S aureus bacteremia had no significant impact on patient outcome as measured by in-hospital mortality after adjustment was made for major confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
159
5
9

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(185 citation statements)
references
References 66 publications
(94 reference statements)
12
159
5
9
Order By: Relevance
“…25,28,44 In our study, even though quantitative use of several antibiotic classes and antibiotics as a whole was much heavier in the MRSA group, no quantitative index emerged as independent predictor of HCA-MRSA infections. Graffunder et al showed that quantitative use of levofloxacin was independently associated with MRSA infection.…”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“…25,28,44 In our study, even though quantitative use of several antibiotic classes and antibiotics as a whole was much heavier in the MRSA group, no quantitative index emerged as independent predictor of HCA-MRSA infections. Graffunder et al showed that quantitative use of levofloxacin was independently associated with MRSA infection.…”
Section: Resultscontrasting
confidence: 70%
“…These two factors, especially the former, are, without any doubt, among the strongest predictors of MRSA infections in older and newer studies. 4,[9][10][11][12][13][14][15][16][17][18][20][21][22][23][25][26][27][28]33,34 Obviously, differences in our results compared to the above-described studies may be partly due to different study design and differences in populations studied, as noted in a recent meta-analysis. 38 Additionally, from a subanalysis of the blood isolates of our study groups, the mean number of antibiotic-days did emerge as independent predictor of a subsequent HCA-MRSA bacteremia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meticillin-resistant Staphylococcus aureus (MRSA) remains a leading cause of healthcare-acquired infection and affects the most vulnerable patients with significant morbidity and mortality (Harbarth et al, 1998;Cosgrove et al, 2003;Salgado et al, 2003;Cooper et al, 2004; Francois et al, 2007). Despite the lack of convincing evidence (Coia et al, 2006), it is now accepted that a major aspect of controlling the spread of MRSA is the prompt identification of patients at risk of MRSA carriage (Chaix et al, 1999;Cepeda et al, 2005;Malde et al, 2006;Cunningham et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the reality is that various external factors such as sample collection, transport, reception, documentation and reporting significantly increase the real reporting time, making the target of same-day reporting difficult to achieve (Harbarth et al, 1998; Jeyaratnam et al, 2008;Aldeyab et al, 2009 Only patients who were routinely screened for MRSA were included. The study was carried out in full accordance with clinical governance as stated by NHS Lothian.…”
Section: Introductionmentioning
confidence: 99%